Sejarah Sosial Politik Kerajaan Majapahit - Setiawan, Zudi (JURNAL LANSKAP POLITIK, 2022)
The greatness of the Majapahit empire has been a source of inspiration for Indonesia's past glory which was formed as a state in the following centuries after the fall of Majapahit. Modern Indonesian nationalists, including those involved in the National Awakening Movement in the early 20th century, have pointed to Majapahit as a shining example of the past glories of the Indonesian nation. Like Majapahit, the Republic of Indonesia covers a large area and is politically centered on the island of Java. The Majapahit Empire is not only an icon of the heyday of Javanese-Hindu civilization, but also historical evidence of the socio-political struggles that occurred in the process of Islamization in the Nusantara.